2020
DOI: 10.1155/2020/9171027
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic Effect of Lead and Cadmium on Workers at Wastewater Plant in Iraq

Abstract: Heavy metal poisoning is a worldwide problem that is caused by different human industrial activities such as battery and painting manufacturing and occupational exposure of those working at petrol stations. Wastewater is known to contain higher amounts of heavy metals such as lead (Pd) and cadmium (Cd) and might be sources of exposure for workers at the wastewater treatment plant. However, to our best knowledge, no studies were done to evaluate the level of cadmium and lead in blood of workers at wastewater tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…The International Agency for Research on Cancer (IARC) has classified Pb as a possible human carcinogen (group 2B) and its inorganic compounds as probable human carcinogens (group 2A). The genotoxic effects of Pb have been investigated for many years and include chromosome aberration (CA), mutation, DNA breakage, and DNA synthesis inhibition [ 14 , 15 ]. According to previous studies, the end-points of the genotoxic effects of Pb have been well-demonstrated in different in vitro, in vivo, and epidemiological studies.…”
Section: Genotoxicity Of Leadmentioning
confidence: 99%
See 1 more Smart Citation
“…The International Agency for Research on Cancer (IARC) has classified Pb as a possible human carcinogen (group 2B) and its inorganic compounds as probable human carcinogens (group 2A). The genotoxic effects of Pb have been investigated for many years and include chromosome aberration (CA), mutation, DNA breakage, and DNA synthesis inhibition [ 14 , 15 ]. According to previous studies, the end-points of the genotoxic effects of Pb have been well-demonstrated in different in vitro, in vivo, and epidemiological studies.…”
Section: Genotoxicity Of Leadmentioning
confidence: 99%
“…8-OHdG is one of the predominant forms of oxidative lesions and has been widely used as a biomarker for oxidative stress [ 26 ]. Several studies demonstrated a positive relation between 8-OHdG and Pb [ 15 , 27 , 28 ]. The DNA repair machinery plays the crucial role of protecting the cells from DNA damage generated by exposure to carcinogens and cytotoxic agents, as well as heavy metals.…”
Section: Genotoxicity Of Leadmentioning
confidence: 99%
“…By inhibiting δ-aminolevulinic acid dehydratase, Pb favours the accumulation of ALA, which triggers ROS production, but also acts as a carcinogen (116). ALA-mediated oxidative DNA damage occurs through the production of 8-OHdG, 8-hydroxyguanine (8-oxo-7,8-dihydroguanine), and 8-oxo-7,8-dihydro-2deoxyguanosine (8-oxodG) (116,152). A number of studies has reported positive correlation between ALA levels and markers of oxidative stress and carcinogenesis (116,137,141,153).…”
Section: Mechanism Of Carcinogenicitymentioning
confidence: 99%
“…ALA-mediated oxidative DNA damage occurs through the production of 8-OHdG, 8-hydroxyguanine (8-oxo-7,8-dihydroguanine), and 8-oxo-7,8-dihydro-2deoxyguanosine (8-oxodG) (116,152). A number of studies has reported positive correlation between ALA levels and markers of oxidative stress and carcinogenesis (116,137,141,153). Furthermore, hydroxyl radicals (HO•) generated by ALA attack DNA strands and interact with its nucleobases to produce various oxidation products.…”
Section: Mechanism Of Carcinogenicitymentioning
confidence: 99%
See 1 more Smart Citation